Assessment of the teaching methods impact on the level of financial literacy - Irina K. Bitkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper contains the results of the study to assess the impact of teaching methods on the level of students functional literacy. The relevance of the research is determined by the importance of developing a scientific basis for the preparation of modern higher education training programs aimed at developing the rigid and flexible skills of future specialists. Based on the analysis of domestic and foreign scientific sources and accumulated pedagogical experience, the features and components of the concept of functional literacy are identified, on the basis of which a conclusion is made about the complex nature of this concept. This character allows us to apply various forms to assess the achievement of the functional literacy concept components. This approach was realized during our experiment, the results of which are reflected in this paper. Currently, in pedagogical science, the influence of various forms of education on the functional literacy level of students has been studied to an incomplete degree. The aim of the study was to assess the impact of teaching methods on the functional literacy level of students. The basic research method is a scientific experiment. Classical and innovative (interactive) forms and technologies of practical classes were used as the experimental material. Two groups of students of Economics specialty were chosen as the object of research during their final year. To achieve the purpose of the study, a sequential multi-stage study was conducted. Based on the results of the study, recommendations were made about the possibility of using various forms of education in order to improve the functional literacy of students. The possibilities of using interactive forms of education to improve the functional literacy of students of socio-humanitarian areas of training are revealed.